Power flow controller based on a new proposed statcom controller - Y.Suliman, Mohammed; Khalil Antar, Rakan (International Journal of Engineering and Technology, 2018)
One of the major issues involved in power transmission systems are enhancing the capability of transfer and flexible control of active power through the existing transmission line system. To achieve these goals, power electronics devices for reliable operation and faster control are used and utilized to control the flow of power under the flexible ac transmission systems. STATCOM based on voltage source inverter can compensate a controllable voltage over the identical range of capacitive and inductive independently of the line cur-rent. In this paper, a new proposed scheme of STATCOM using Neuro-Fuzzy logic controller is proposed and trained off-line based on Sugeno type fuzzy logic rules. In addition, dq theory is used to calculate the power system parameters due to its less computation and high accuracy. The simulation results show that the proposed controller is reliable and robust compared with the conventional controllers that are investigated previously.